ANALISIS PENDAPATAN DAN NILAI TAMBAH AGROINDUSTRI KERIPIK PISANG (STUDI KASUS PADA UKM SELERAKU BANJARNEGARA) - Sarno, Sarno; Kinding, Dwi Putriana Nuramanah; Solekan , Muhamad (Jurnal Saintifik (Multi Science Journal), 2024)
UKM Seleraku is one of the businesses engaged in the agro-industry of banana chips in Banjarnegara Regency. The fundamental issue faced by UKM Seleraku is the lack of knowledge regarding the overall production costs and added value of the banana chips agro-industry they are involved in. The research aims to analyze the income and added value of the banana chips agro-industry. The basic research methods applied include case study and descriptive methods, as well as participatory action research. Data collection methods involve interviews, direct observation, and record-keeping. The data used in this research consists of two types: primary data and secondary data. The data analysis includes cost analysis, revenue analysis, income analysis, and added value analysis. Based on the research results, the findings are as follows: (1) UKM Seleraku incurs a total production cost for banana chips agro-industry amounting to IDR 10,090,000 per month, with fixed costs of IDR 3,350,000 and variable costs of IDR 6,740,000, (2) The total revenue generated by UKM Seleraku from the banana chips agro-industry is IDR 12,775,000 per month, while the income obtained is IDR 2,265,000 per month, (3) The added value of UKM Seleraku's banana chips agro-industry is IDR 68,750 per kilogram, calculated as the difference between the product value and the raw material cost, as well as other input values. This means that each kilogram of input (banana) generates an output (banana chips) worth IDR 68,750. The added value contributes 48.50 percent to the average output value in each production process. The added value ratio reaching 48.50 percent indicates the high value added from processing bananas into banana chips.